IMPACT OF MATERNAL DEPRESSION ON GROWTH OF THE CHILD (The Research of Medical Science Review, 2025)
Depression is common in women of reproductive age in developing and developed countries. As mothers are primary care takers of their children, they play a significant role in growth of the child. Therefore, mothers who are depressed can adversely affect the growth of the child. OBJECTIVE: To assess the prevalence of maternal depression and its effect on growth of the child in developing countries such as Pakistan. METHOD: 84 participants in JMCH Korangi who met our inclusion criteria were given a consent form. We read out and explained everything to illiterate participants and their thumb prints were taken. The weight of the babies aged between 3 months to 36 months were plotted on a growth chart and their mother’s depression was assessed using ICD-10 and PHQ-9 questionnaire. We used SPSS version 25 to analyze the data. RESULT: 56% of mothers were depressed out of which 70.2% of the babies were below 3rd; 10.7% were mildly depressed with 13.6% children below 3rd percentile, 29.8% were moderately depressed with 38.6% children below 3rd percentile, 11.9% were moderately severely depressed with 15.9% children below 3rd percentile, 3.6% were severely depressed with 6.8% children below 3rd percentile. 29.8% were above 3rd percentile. CONCLUSION: Our data concludes that there is an association between maternal depression and the growth of a child. It was found that the children who were below the 3rd centile had mothers who were dealing with depression.